San Jose City College 1989 - Cinco de Mayo Performance (and Other Events) - Castellano, Alcario:::creator:::::::::::: (2024)
Video and transcripts of a Cinco de Mayo performance at San Jose City College in 1989. Also included is a video of a Cinco de Mayo Installation artpiece by Diana Argabrite (40:53) and a video of an eight person orchestra (45:06). And science lecture (1:37:15).